Die etos van die Nederduitsch Hervormde Kerk - Koekemoer, J. H. (Hervormde teologiese studies, 1995)
The ethos of the Nederduitsch Hervormde Kerk. In this article two aspects of the Reformed ethos of the Nederduitsch Hervormde Kerk van Afrika come to the fore. First, attention focuses on truth as encounter. Truth is not something neutral but something that involves the self, and is as such apprehended not by a solitary intellect, but by the whole person in fellowship with God. In the second place attention is given to the importance of the confessional tradition and its interpretation in Reformed theology.